Early Phase Cancer Immunotherapy (Current Cancer Research,, 2018)
This volume, a state-of-the-art review of early phase clinical trials for cancer immunotherapy, discusses biomarker selection, combinatorial strategies and their safety or toxicity, determination of Phase 2 dosing, endpoints in the setting of radiographic pseudoprogression, histology selection, and novel immunotherapeutics as they relate to early phase cancer immunotherapy.